That they may be one (Jn 17:11): Mending the seamless coat of Christ in Assemblies of God Nigeria - Ituma, Ezichi A. (HTS teologiese studies, 2023)
Assemblies of God church in Nigeria, which has for over 40 years now, experienced various crises that have led to sucession and factionalism in that church. The once giant of spirituality and the mother of Pentecostalism has grappled with the problem of administration, leadership tussle and bigotry. This study is a review of previous and current crises that AG Nigeria has gone through at the General Council level in a bid to mend what seems to have torn asunder the seamless coat of Christ in line with the prayer of Jesus, ‘that they may be one’. The study uses historical-critical method and phenomenological design to analyse the depth of the crack in the church in order to predict the future of Pentecostalism in Nigeria.Contribution: To chronicle the crises in Assemblies of God Nigeria through a study of current and past patterns of events with a view to recommending possible solutions.